2017
DOI: 10.1002/ange.201612235
|View full text |Cite
|
Sign up to set email alerts
|

Batch and Continuous‐Flow One‐Pot Processes using Amine Diazotization to Produce Silylated Diazo Reagents

Abstract: An ovel synthesis of trimethylsilyldiazomethane (TMSCHN 2 )b yd iazotization of trimethylsilylmethylamine (TMSCH 2 NH 2 )i sr eported using batch and continuous flow synthesis.T he latter affords ad aily production of 275 g (2.4 mol) of TMSCHN 2 .O ther silylated methylamines were also successfully reacted under the developed reaction conditions to furnish various silicon-bearing diazomethane reagents.T he applicability of the process is highlighted by disclosure of batch and continuous flowone-pot esterificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Thus,such reactive compounds are ideally not stored in large quantities on site,a nd just-in-time syntheses are preferred. [17][18][19][20][21][22][23][24][25][26][27] Thep rice of the soluble dirhodium catalysts (Rh 2 L 4 ,L= ligand) is another barrier for industrial applications.R hodium is av ery expensive noble metal and the cost for the synthesis of these ligands for the catalysts also cannot be ignored. To recycle the homogenous dirhodium catalysts, additional separation steps are required and the catalytic activities are often not maintained after recovery and recycle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus,such reactive compounds are ideally not stored in large quantities on site,a nd just-in-time syntheses are preferred. [17][18][19][20][21][22][23][24][25][26][27] Thep rice of the soluble dirhodium catalysts (Rh 2 L 4 ,L= ligand) is another barrier for industrial applications.R hodium is av ery expensive noble metal and the cost for the synthesis of these ligands for the catalysts also cannot be ignored. To recycle the homogenous dirhodium catalysts, additional separation steps are required and the catalytic activities are often not maintained after recovery and recycle.…”
mentioning
confidence: 99%
“…Several studies have recently reported expanding the utilization of diazo compounds in flow; however, the subsequent diazo-consuming reactions were conducted in abatch reactor with homogenous catalyst. [17][18][19][20][21] Relatively few reports have tried to increase the TONo fd irhodium catalysts for CÀHf unctionalization by immobilization of the catalysts. [29][30][31][32][33] These studies have mainly focused on the catalytic performance of the immobilized catalyst with diazo compounds.T ot he best of our knowledge,n oo ne has resolved all the challenges stated above to date;herein, we introduce ascalable flow process for CÀHf unctionalization with dirhodium catalysts by developing cascade reactions employing microfluidic flow reactor systems.Scheme 1describes the overall cascade reaction in aflow system for selective C À Hf unctionalization.…”
mentioning
confidence: 99%
“…Recently, we delineated the synthesis of trimethylsilylmethylammonium chloride from trimethylsilylmethyl chloride and ammonium hydroxide in a continuous flow process (Scheme 1). 6 Continuous-flow technologies enable rapid reactions with excellent heat transfer, facilitate the manipulation of gas, and often decrease the formation of byproducts. 7−10 Herein, we report a general amination procedure in flow, applicable to various electrophiles (alkyl halides and epoxides) with ammonia and hydroxylamine.…”
mentioning
confidence: 99%
“…We first investigated the amination of phenethyl bromide with ammonia under the previously developed reaction conditions. 6 Low yields were obtained with the formation of the secondary ammonium salt (resulting from the double addition of ammonia to the bromide) as the major byproduct (Table 1, entry 1). When the concentration of the bromide was decreased to 0.25 M (thus increasing the number of equiv of ammonium hydroxide from 28 to 56 equiv) with a 30 min residence time, the yield increased to 74% (entry 2).…”
mentioning
confidence: 99%
“…29 However, after a range of preliminary experiments involving TMS 13 CH2X (X = Cl, Br, I) we pursued an alternative route based on amine diazotization. 30 The requisite 13 C-labelled amine (11) was prepared via a multistep chromatography-free sequence, starting from 13 CH3OH (7), Scheme 3. With the amine 11 in hand, we utilized Lebel's diazotization procedure, and after careful re-optimization for 13 C-labelled synthesis 31 prepared a large stock solution of [ 13 C]-TMSDAM (12, 0.6M in 2-Me-THF; dried over molecular sieves).…”
Section: Resultsmentioning
confidence: 99%